2006
DOI: 10.1111/j.1540-6237.2006.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

College, Jobs, or the Military? Enlistment During a Time of War*

Abstract: Objective. This article questions what factors are associated with joining the military after high school rather than attending college, joining the civilian labor force, or doing some other activity. Three areas of influence on military enlistment are highlighted: educational goals, the institutional presence of the military in communities, and race and socioeconomic status. Method. The analysis uses data from a recent cohort of high school graduates from the State of Texas in 2002, when the United States was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
121
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(130 citation statements)
references
References 23 publications
9
121
0
Order By: Relevance
“…Furthermore, according to Segal, Bachman, & O'Malley (1999), the presence of a military parent, military grandparent or a military sibling within the family increases the propensity of a potential enlistee to enlist. This is consistent with more recent studies such as Kleykamp (2006) and Cebula, Menon, & Menon (2008) indicating that the institutional and cultural presence of the military within an area has a significant influence on the enlistment decisions made by youths.…”
Section: Research In Applied Economicssupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, according to Segal, Bachman, & O'Malley (1999), the presence of a military parent, military grandparent or a military sibling within the family increases the propensity of a potential enlistee to enlist. This is consistent with more recent studies such as Kleykamp (2006) and Cebula, Menon, & Menon (2008) indicating that the institutional and cultural presence of the military within an area has a significant influence on the enlistment decisions made by youths.…”
Section: Research In Applied Economicssupporting
confidence: 81%
“…The analysis furthers the idea that black youths regard the military as a vehicle for upward social and economic mobility and therefore are more likely to enlist in the military compared to white youths. This finding is consistent with Kleykamp (2006). Furthermore, according to Segal, Bachman, & O'Malley (1999), the presence of a military parent, military grandparent or a military sibling within the family increases the propensity of a potential enlistee to enlist.…”
Section: Research In Applied Economicssupporting
confidence: 79%
“…Enlistees are highly self-selected. Men who choose military service differ systematically from those who go to work or enroll in college (Kleykamp 2006;. Enlistees tend to have lower socioeconomic status, non-college-educated parents, lower grades and no college plans (Bachman et al 2000;Kilburn 1992;Kilburn and Asch 2003;Kilburn and Klerman 1999;Teachman, Call, and Segal 1993a,b).…”
Section: Selectionmentioning
confidence: 99%
“…Propensity can be general, relating to service in the military at large, or it can be specific to a specific branch of the Armed Forces (Shavelson, Haggstrom, and Winkler, 1983). Living near military installations increases propensity (Kleykamp, 2006), indicating that there are expected regional differences in propensity due to the regional asymmetric distribution of military bases. Segal, Bachman, Freedman-Doan, and O'Malley (1999) note that propensity is generally stable across time when measured at the state or National level, though in some subgroups (based on ethnicity and gender), generational shifts have been observed.…”
Section: Army Recruitingmentioning
confidence: 99%
“…The options available for potential Army recruits to choose from might be summarized as education, employment, or enlistment; propensity is the predisposition to make a choice to join the Army (and so, while this variable is binary categorical for an individual, when aggregated to a population it is a continuous measure of the estimated percentage of the youth population that are predisposed to join and would state so if asked in a survey). This choice can be influenced by many factors: Asch, Kilburn, and Klerman (1999) argued that the military is often in direct competition with universities for the best educated youth graduating high schools; Kleykamp (2006) conducted a study in Texas and found that expected increases in education costs often lead young people to use the military instrumentally to facilitate later education, further highlighting the relationship between the three options. Orvis, Sastry, and McDonald (1996) defined propensity as an overall measure that summarizes an individual's initial interest to join.…”
Section: Army Recruitingmentioning
confidence: 99%